Selective capture of iodate anions by a cerium-based metal-organic framework - Zhao Yuting; Li Jie; Chen Long; Guo Qi; Li Lingyi; He Linwei; Zhai Fuwan; Zhang Mingxing; Chai Zhifang; Wang Shuao (National Science Open)
Effective remediation of radioactive IO3− is highly desirable for fuel reprocessing, medical waste disposal, and nuclear accidents. However, the nature of high solubility, strong mobility, and extremely hard to bind with minerals for IO3− makes this task an enormous challenge. Herein, a metal-organic framework material [Ce(IV)-MOF-808] with available Ce(IV) sites was used to efficiently remove IO3−. Ce(IV)-MOF-808 exhibits superior selectivity and one of the highest adsorption capacities (623 mg·g−1) for IO3− removal. Moreover, Ce(IV)-MOF-808 shows great adsorption performance for IO3− at low concentrations, and the distribution coefficient (Kd) value was calculated to be 2.60 × 106 mL·g−1. The exceptional IO3− uptake performance is attributed to the high affinity between Ce(IV) cluster and the oxyanion based on the comprehensive analysis of zeta potential and X-ray photoelectron spectroscopy (XPS) results, in which IO3− can easily replace the weakly coordinated ligand and form a strong coordination structure of Ce-O-I-O2. More importantly, Ce(IV)-MOF-808 exhibits excellent uptake performance for IO3− from both the simulated Beishan groundwater system and Hanford groundwater system in the dynamic column separation test, indicating the highly promising practical application of Ce(IV)-MOF-808 in IO3− remediation from actual radioactive wastes.